Gênero, feminismos e necessidades de saúde: a perspectiva das mulheres atendidas em um Centro de Atenção Psicossocial Álcool e Drogas (CAPS AD) - Cugler, Priscila Souza (2018)
It is possible to identify the gender differences related to the use of psychoactive substances (SPA), such as the reason for use, comorbidities, cultural and physical factors. The SPA health policy indicates that it is invisible and homogenizing, and women face structural, systemic, social, cultural and personal barriers in the search for and permanence in treatments. The purpose of this research was to understand the health needs of women treated in a CAPS AD, to characterize their conceptions about the use and the repercussions for health. The theoretical framework articulated the understanding of gender and feminist movements, with the interweaving of health needs and conceptions of psychosocial attention. The methodology was the oral history of life, with the accomplishment of open interviews with nine women, for the apprehension of narratives about their life experiences. The interpretation of the data was the analysis of thematic content, in which it was possible to identify four thematic categories: 01) Psychosocial Phenomena, the points identified, as health need, were to strengthen family and affective bonds, the process of experiencing mourning, as well as to offer spaces for socialization and acceptance and Gender Violence is also a phenomenon to be taken considered concerning social health needs, taking into account the traumas experienced throughout life, the affective issues and the specificities of gender inequalities; 02) The Maternity Experience Phenomenon points out that motherhood is a health need because of its relation to the historical dimension of sexual and reproductive rights and the experienced stigmas, revealing the problems that raise when the right to be a mother is denied; 03) Regarding to the Health Repercussions - health needs are related to eating disorders, liver diseases, falls with fractures, difficulty in attention and memory, and hangover effects, as well as melancholy, sadness and loneliness in their different manifestations, such as suicidal ideation, depression and bipolar disorder and 04) Mechanisms for the Strengthening of Autonomy, the process of greater self-awareness and insertion into productive activities are strategies for health care, rescuing and valuing their potentialities. The perspective of the affections and bond with the relatives is an important action of to be problematized. We can identify that gender inequalities became evident in cases of violence, of financial dependence, of multiple roles with work and children, of demand to meet beauty standards, in the differences in work and income opportunities, and stigmatization through the use of SPA and family ties. These social and historical constructs of gender reflect the daily actions of women, and for some of them, consciously or not, the way of coping occurs through the use of SPA. From the perspective of psychosocial care, we seek to contribute to women and professionals who are ethically and technically involved in the care process, and in the clinic management, by overcoming the hegemonic forms of health care, offering improved listening and accountability of care for women